2023
DOI: 10.35516/hum.v50i3.5413
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Social Media and Their Relation to Family Disintegration: Perspectives from Families in Northern Jordan

Abstract: Objectives: This study investigates the relationship between social media (SM) and family disintegration from the perspectives of Jordanian families in Irbid city, located in the north of Jordan. It explores this relationship in light of various variables, including gender, age, family's monthly income, and educational level. Methods: The study sample consisted of 294 fathers and mothers randomly chosen from Irbid city. A questionnaire was used as a means of data collection. Results: The study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…In addition, the research done in Jordan also showed that social media is a factor leading to family instability, highlighting its involvement in causing conflicts within families, enabling sexual deviations among youngsters, promoting unhealthy marriage relationships, and impacting children's well-being. The act of defying paternal authority, escalating instances of spousal unfaithfulness among both genders, and the actions in question potentially erode the ethical and cultural framework underpinning Jordanian family units (Al Khataybeh, Obeidat, Al-Zubaidi, & Aljedayah, 2023).…”
Section: Infidelitymentioning
confidence: 99%
“…In addition, the research done in Jordan also showed that social media is a factor leading to family instability, highlighting its involvement in causing conflicts within families, enabling sexual deviations among youngsters, promoting unhealthy marriage relationships, and impacting children's well-being. The act of defying paternal authority, escalating instances of spousal unfaithfulness among both genders, and the actions in question potentially erode the ethical and cultural framework underpinning Jordanian family units (Al Khataybeh, Obeidat, Al-Zubaidi, & Aljedayah, 2023).…”
Section: Infidelitymentioning
confidence: 99%